2019
DOI: 10.1136/archdischild-2018-316757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a mobile application for heart rate assessment in simulated neonatal resuscitation: a randomised controlled cross-over study

Abstract: BackgroundClinical assessment of newborn heart rate (HR) at birth has been reported to be inaccurate. NeoTapAdvancedSupport (NeoTapAS) is a free-of-charge mobile application that showed good accuracy in HR estimation. This study aimed to evaluate the impact of NeoTapAS on timing of HR communication and resuscitation interventions.MethodsThis was a randomised controlled cross-over (AB/BA) study evaluating HR assessment using auscultation plus NeoTapAS compared with auscultation plus mental computation in a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(29 reference statements)
0
8
1
Order By: Relevance
“…Training apps improve performance in both knowledge-based and scenario-based simulations, 12 13 and our findings support this. Furthermore, our study had a comparable categorical error rate as the NeoTapAvancedSupport, 14 an HR estimation app.…”
Section: Discussionmentioning
confidence: 98%
“…Training apps improve performance in both knowledge-based and scenario-based simulations, 12 13 and our findings support this. Furthermore, our study had a comparable categorical error rate as the NeoTapAvancedSupport, 14 an HR estimation app.…”
Section: Discussionmentioning
confidence: 98%
“…The NeoTapLifeSupport (NeoTapLS; Tap4Life, Stockholm, Sweden) smartphone app was downloaded from App Store (Apple, Cupertino, CA) and paired with the digital stethoscope for HR assessments. NeoTapLS is a recent development for HR assessment, however has only been tested in high-fidelity resuscitation simulation scenarios (16, 1921). NeoTapLS displays a HR generated by at least three taps on the smartphone screen, which coincides with what the healthcare provider auscultates.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, cost-effective and universally accessible assistive technology (e.g., tap-based smartphone and mobile apps) represent another approach to assess HR in newborn infants (16). Simulation studies reported that it is feasible to assess HR using tap-based smartphone applications (1921). However, this technology has yet to be tested in vivo or during asphyxia in a neonatal model.…”
Section: Introductionmentioning
confidence: 99%
“… 23 24 In 2019, another simulation study showed that NeoTap reduced the time to the first HR and the time to initiate heart compressions and to administer epinephrine compared with auscultation and mental computation. 25 A porcine model showed that HR assessment with NeoTap had similar accuracy compared with auscultation with a digital stethoscope, ECG or carotid blood flow during asphyxia and faster acquisition time compared with the 6 s or 10 s method with a digital stethoscope. 26 However, data on the clinically important group of HR <60 bpm are few and show contradictory results in the studies above as well as in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…22 NeoTap has shown promising results from three simulation studies and an animal model. [23][24][25][26] The aim of our study was to evaluate NeoTap by determining the speed and accuracy at which users could assess a rhythm by a metronome (low-end users, midwives well familiar with neonatal resuscitation but with no prior experience of the tapping method), HR in breathing neonates (high-end users, paediatricians well familiar with the tapping method), and HR in neonates in need of positive pressure ventilation (PPV), equal to neonates with insufficient or no breathing at birth (low-end users). The hypothesis was that NeoTap is as fast or faster than PO and ECG and accurate enough to guide neonatal resuscitations.…”
Section: Introductionmentioning
confidence: 99%